Frequency of primary headaches associated with pain related to disability in the cervical spine - Castro, Ryan pinheiro; Paz, Daniele Da Silva Da; Costa, Camila Vitória de Moraes; Nogueira, Matheus Rafael Feques Ferreira; Alves, Geovanna Cristina Pereira; Cardoso, Thayllane Costa; Andrade, Rodrigo Sousa; Pinto, Guilherme Gonçalves Silva; Gondim, Louise Aline Romao; Paz, Bruna Katarine Beserra; et al. (Headache Medicine, 2024)
Introduction: The literature indicates that individuals with headache have reduced range of motion (ROM) and neck pain, but it is not yet well established whether these conditions reflects on functionality of the cervical spine in young adults. Objective: To evaluate the frequency of disability-related pain in the cervical spine in individuals with and without headache. Materials and methods: Cross-sectional study, young adult individuals with and without primary headaches of both sexes, aged between 18 and 30 years old, were included; those who had secondary headaches and cognitive impairment that made it impossible to complete the questionnaire were excluded. The Visual Numerical Scale (VNS) was used to indicate the intensity of neck pain; the Headache Screening Questionnaire (HSQ) for headache screening and the Neck Disability Index (NDI) to indicate disability related to the cervical spine. The difference between groups was compared using analysis of variance (ANOVA). The level of statistical significance was p≤ 0.05. Results: 89 individuals were evaluated, divided into a headache group (GCC) n=45, with a mean neck pain, age, weight and height of 3.58±3.00, 22.49 years, 64.27kg and 1 62m2 respectively, and control group (CG) n=44 with an average age, weight and height of 22.7 years, 68.41kg and 1.66m2 respectively. There was no significant difference in the levels of disability related to cervical spine pain between the groups. Conclusion: We observed that individuals with tension-type or migraine headaches have mild disability in the cervical spine, and these do not present a significant difference when compared to individuals without headache.